COMMODITY PROSPECTS OF ACEH PROVINCE DURING THE COVID-19 PANDEMIC - Ichsan, Ichsan; Nur Ilham, Rico (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2021)
Food security in households can be measured by maintaining stability and security in the availability of staple food. Covid-19 has an impact on the agricultural sector and farmers so that it affects their income, and automatically changes the availability of food in their households. The purpose of this study was to find out how Covid-19 had an impact on the food availability of rice farmers' households, and what strategies were used to survive in conditions of uncertainty. This research uses a case study approach in Aceh Province. The results of this study show contradictory responses based on the status of the farmer (agriculture as the main or secondary livelihood), and the availability of access to other sources of income affects how or not Covid-19 affects their lives. This study shows that the cultural factors of farmers who live simply and farmers of food commodities are those who are more resilient than farmers of other commodities and the lower middle class in general. The strategy in question is to sell produce with a larger proportion due to declining selling prices, take food from the harvest and rice barns also receive assistance from the government.